2007
DOI: 10.1002/art.22692
|View full text |Cite
|
Sign up to set email alerts
|

Functional defect of circulating regulatory CD4+ T cells in patients with Wegener's granulomatosis in remission

Abstract: Objective. Accumulating data support the role of regulatory T cells, a subset of CD4؉ T cells that expresses CD25high and the transcription factor forkhead box P3 (FoxP3), in controlling and preventing autoimmunity. In Wegener's granulomatosis (WG), an autoimmune vasculitis, up-regulation of CD25 on circulating CD4؉ T cells has been observed, even in patients in remission. The objective of this study was to test whether the frequency and/or function of Treg cells from WG patients in remission are disturbed.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
117
3
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 44 publications
9
117
3
2
Order By: Relevance
“…T cell responses are not suppressed by a population of antigenspecific Treg cells, unlike the effector T cells in Goodpasture's disease, a "one hit" autoimmune disease (15). Similar findings demonstrating ineffective Treg cell suppression have been obtained in patients with Wegener's granulomatosis (WG), in whom functional defects in Treg cells have been demonstrated during disease remission, despite augmented numbers of circulating CD4ϩCD25ϩ FoxP3-expressing Treg cells (27). However, unlike the Treg cells in WG patients, we found that the isolated Treg cells from MPO AAV patients were equally capable of suppressing nonspecific responses.…”
Section: Discussionmentioning
confidence: 61%
“…T cell responses are not suppressed by a population of antigenspecific Treg cells, unlike the effector T cells in Goodpasture's disease, a "one hit" autoimmune disease (15). Similar findings demonstrating ineffective Treg cell suppression have been obtained in patients with Wegener's granulomatosis (WG), in whom functional defects in Treg cells have been demonstrated during disease remission, despite augmented numbers of circulating CD4ϩCD25ϩ FoxP3-expressing Treg cells (27). However, unlike the Treg cells in WG patients, we found that the isolated Treg cells from MPO AAV patients were equally capable of suppressing nonspecific responses.…”
Section: Discussionmentioning
confidence: 61%
“…Several studies have been performed on Tregs in vasculitis. In patients with Wegener's granulomatosis in remission an expanded proportion of regulatory T cells that are functionally defective was found [90]. In addition, in patients with active Churg-Strauss syndrome, regulatory T cells producing interleukin-10 are detected rarely compared with patients with chronic eosinophilic pneumonia and/or asthma [91].…”
Section: Cd28mentioning
confidence: 99%
“…While AAV is characterized (and defined) by autoantibody formation, cellular immunity is critical for the development of autoimmunity and renal injury (5)(6)(7). Furthermore, while antineutrophil cytoplasmic antibody (ANCA) characterizes (and defines) the disease, the vasculitis involving the glomerular capillary bed has little or no antibody deposited, but rather demonstrates infiltration of delayed-type hypersensitivity (DTH) effector cells and fibrin.…”
mentioning
confidence: 99%